A dual-channel fluorescent ratio probe with hypoxia targeting and hypoxia activation capacity for tumour imaging. Issue 22 (24th May 2022) - Yuan, Pengcheng; Xu, Xiaodan; Xiao, Bing; Shi, Xueying; Zhang, Wei; Xu, Hongxia; Piao, Ying; Shen, Youqing; Slater, Nigel K. H.; Tang, Jianbin
Abstract : Illustration of the fluorescent ratio probe (OPDEA/BOD-NO2 ) with hypoxia targeting and hypoxia activation capacity for in vivo tumour imaging. Abstract : Efficient hypoxia diagnosis is a great challenge for nearly all solid tumours due to operability, permeability and specificity. Although some inspiring approaches have been explored to date, it is the first time that a dual-channel NIR probe (denoted as OPDEA/BOD-NO2 ) simultaneously with hypoxia targeting and activation capacity was employed to realize effective prolonged hypoxia ratio imaging in the present work. OPDEA/BOD-NO2 consists of hypoxia-targeting tertiary amine N -oxide based polymers and nitrobenzene modified Aza-BODIPY (BOD-NO2 ). OPDEA/BOD-NO2 had strong red fluorescence at λ ex = 660 nm and λ em = 710 nm, while it turned into another fluorescent Aza-BODIPY dye (BOD) with strong NIR fluorescence at λ ex = 720 nm and λ em = 790 nm in hypoxia microenvironment, providing two channels with big Stokes shift for hypoxia ratio imaging and monitoring probe distribution and activation, respectively. Meanwhile, hypoxia-targeting tertiary amine N -oxide based polymers could effectively enhance tumour accumulation (2.99-fold, 660 nm; and 2.74-fold, 720 nm) for prolonged hypoxia ratio imaging with obviously improved signal-to-background ratio within 48 hours, which is much better than that of PEG/BOD-NO2 .